Conservation status of the order Rodentia of Brazil: taxonomic and biogeographical patterns - Lacher, Thomas Edward; McCay, Shelby D.; Bianconi, Gledson Vigiano; Wolf, Lilianna K.; Roach, Nicolette S.; Percequillo, Alexandre Reis (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2020)
The Global Mammal Assessment (GMA) evaluates the risk of extinction for all species of mammals, providing important data on their status to national and global conservation agencies and conventions. We assessed all of the species of Brazilian rodents as part of the GMA activities of the International Union for the Conservation of Nature Species Survival Commission (IUCN SSC) Small Mammal Specialist Group. A total of 234 species were evaluated against the IUCN Red List Criteria and placed into one of eight categories. Although rodents do not have elevated extinction risk compared to mammals as a whole, several families of caviomorph rodents have high levels of either threat, data deficiency, or both. The family Echimyidae has a large number of species and one-third of those either are species of conservation concern or data deficient. The family Ctenomyidae also is of concern in this regard. There are also strong geographic patterns to threat and poor knowledge. The focal areas for conservation effort are the Atlantic Forest and the Cerrado, and for Data Deficient species Atlantic Forest, Cerrado, and Amazonia, in particular the eastern Amazon. The results highlight the need for targeted field research and the application of ecological and spatial data to the development of conservation actions.